KAJIAN KOTA SEMARANG MENUJU KOTA RAMAH LANSIA - Evi Widowati; Fafurida Fafurida; Galuh Nita Prameswari (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2018)
This research aims to describe the peoples opinion especially elderly towards WHO indicator for an elderly friendly city. The other purposes is giving a recommendation for local government to achieve a goal “elderly friendly city in 2030”. Therefore, the government could arrange a policy and programs to achieve that purpose. The recommendation obtained from KRL indicator description who never been seen before by the government. The research methods is quantitative descriptive with primary data base and purpossive sampling method. The research result show the first indicator of open space and building belongs to the category